Populism, Authoritarianism and Necropolitics - Yilmaz, Ihsan. author. (orcid)0000-0001-8409-3045 Link aut Link
VII, 219 p. 2 illus.
Keywords: This book examines how Turkey’s ruling party, the Justice and Development Party (AKP), under the leadership of Recep Tayyip Erdoğan produces and employs necropolitical narratives in order to perpetuate its authoritarian rule. In doing so, the book argues that as the party transitioned from socially conservative Muslim democratic values to authoritarian Islamism, it embraced a necropolitical narrative based on the promotion of martyrdom, and of killing and dying for the Turkish nation and Islam, as part of their authoritarian legitimation. This narrative, the book shows, is used by the party to legitimise its actions and deflect its failures through the framing of the deaths of Turkish soldiers and civilians, which have occurred due to the AKP’s political errors, as martyrdom events in which loyal servants of the Turkish Republic and God gave their lives in order to protect the nation in a time of great crisis. This book also describes how, throughout its second decade in power, the AKP has used Turkey’s education system, its Directorate of Religious Affairs, and television programs in order to propagate its necropolitical martyrdom narrative. Ihsan Yilmaz is Research Professor and Chair of Islamic Studies at the Alfred Deakin Institute for Citizenship and Globalisation (ADI), Deakin University, Melbourne, Australia. Omer Erturk is an Independent Researcher in Berlin, Germany, with an interest area focused on Turkish politics, Islamist movements in Turkey, relations between politics and religion, radicalism and autocracy.